The Top Ranked 101 Articles in Pediatric Surgical Journals from an Altmetric Perspective - Shu, Boshen; Riedel, Jan; Lacher, Martin; Mayer, Steffi (European Journal of Pediatric Surgery, 2024)
Introduction In the era of scientific digitalization, online media platforms gain increasing popularity to accomplish research output awareness. The Altmetric Attention Score AAS weights these online mentions based on a privy algorithm. We aimed to characterize the top 100 articles with the highest (AAS) published in pediatric surgery journals.Materials and Methods Publications from six core pediatric surgery journals were retrieved from www.altmetric.com in January 2023 and ranked by their AAS. The top 101 publications were analyzed for their bibliometric measures, study design, and quality as well as online media mentions.Results The top 101 AAS articles were published between 1974 and 2022, preferentially from the United States (64%) and mainly in Journal of Pediatric Surgery (73%), followed by Journal of Pediatric Surgery Case Reports, Pediatric Surgery International, Seminars in Pediatric Surgery, and European Journal of Pediatric Surgery. Their AAS ranged between 21 and 389 (median: 33), with Twitter/X being mostly responsible for online mentions (n = 2,189; 75%). The number of citations in peer-reviewed journals ranged between 0 and 358 (median: 16) and did not correlate to AAS. Retrospective study design (33%) with low evidence level IV (43%) dominated.Conclusion The Journal of Pediatric Surgery is the main source of high-profile AAS publications in pediatric surgery. The altmetric popularity of articles is predominantly achieved by their propagation via X, irrespective of the study quality and recognition in the scientific community. Thus, active “twitterism” may play the key role to reach high AAS scores.
Keywords: pediatric surgery; Altmetric Attention Score; online media; level of evidence; Twitter/X